Hurdling the Challenges of the 2019 IAAF World Championships - Girard, Olivier; Racinais, Sebastien (Frontiers Media SA, 2020)
The state of Qatar is preparing to stage the 17th International Association of Athletics Federations (IAAF) World Championships later this year (September 27 to October 6, 2019). While the Qatari capital Doha has an extensive history as a host of international athletics events (from the first ever IAAF Grand Prix in 1997 to the 2010 IAAF World Indoor and the Championships Doha Diamond League over the last decade), the IAAF World Championships will have be bigger in terms of global reach and impact. Doha will be welcoming 205 countries and 3,500 athletes with approximately 10,000 international guests, 30,000 spectators from outside Qatar and more than 2,000 media personnel. These 2019 IAAF World Championships are a fantastic opportunity for the scientific community to provide up-to-date knowledge and propose solutions to solve real-world problems for elite competitors. In particular, athletes are likely to encounter challenging hot temperatures and potentially high humidity levels that may eventually impair performance during middle and long distance events and increase the risk of exertional heat. The IAAF is providing information leaflets explaining various protective or countermeasures to mitigate these risks. Additionally, Doha is working with the IAAF to research innovative new solutions for competition timing, scoring, measurement and television production, using the latest technology. Doha also is determined to further accelerate the growth of women's athletics and Paralympics champions across the region. This may in turn drive the development of new knowledge, using an integrative sports science approach to improve performance of special athletic populations.